Dynamic Inflation and Economic Growth Nexus in Bangladesh - Md. Nezum Uddin (Journal of Accounting, Business and Management (JABM), 2019)
This scholarly article seeks to spotlight the inextricable link between economic expansion and inflation in Bangladesh for the past three decades from 1987 to 2017. The nature of the relationship between these two macroeconomic variables is a boiling topic of research. The data on both the GDP growth and inflation rates supplied by the World Bank have been used to study the nexus. Different relevant tests (DF, ADF, PP and KPSS test) found unit root in the variables, but this problem is disappeared at the first difference. Cointegration tests display the long-run connection between the variables at the period. Max-Eigen value Statistic Trace Statistic expose there may be a second integrating vector. The vector error correction model (VECM) finds short dynamics among inflation and economic development, and the adjustment speed at 39% and 82% respectively for the variables—GDP growth rate and inflation. This empirical study has found a significant correlation between inflation and economic growth in Bangladesh during the study period